2022
DOI: 10.7150/ijbs.67138
|View full text |Cite
|
Sign up to set email alerts
|

Paclitaxel treatment enhances lymphatic metastasis of B16F10 melanoma cells via CCL21/CCR7 axis

Abstract: Chemotherapeutic drugs have been successfully used to treat several cancers, including melanoma. However, metastasis occasionally occurs after chemotherapy. Here, we reported that paclitaxel (PTX) treatment for B16F10 tumour in mice led to an enhanced lymphatic metastasis of the melanoma cells, although a significant inhibition of tumour growth at the injection site was observed. Further study demonstrated that PTX upregulated the expression of C-C chemokine receptor type 7 (CCR7) in B16F10 cells, enhancing th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 47 publications
(62 reference statements)
2
7
0
Order By: Relevance
“…In this report, we demonstrated that inhibition of miR‐590‐5p observably reversed the inhibitory effect of MOE. In addition, it also been reported that CCR7 is associated with immune responses 49,50 . In our data, CCR7 as a target of miR‐590‐5p and overexpression of CCR7 also remarkably reversed the inhibitory effect of MOE.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…In this report, we demonstrated that inhibition of miR‐590‐5p observably reversed the inhibitory effect of MOE. In addition, it also been reported that CCR7 is associated with immune responses 49,50 . In our data, CCR7 as a target of miR‐590‐5p and overexpression of CCR7 also remarkably reversed the inhibitory effect of MOE.…”
Section: Discussionsupporting
confidence: 80%
“…In addition, it also been reported that CCR7 is associated with immune responses. 49,50 In our data, CCR7 as a target of miR-590-5p and overexpression of CCR7 also remarkably reversed the inhibitory effect of MOE. Therefore, our results…”
Section: Discussionsupporting
confidence: 64%
“…Decreased survival associated with the activation of CCR7 is achieved through PI3K/Akt, ERK1/2, JNK and p38 signalling (Figure 2). 107,108 In addition, a previous study, investigating the expression of CCL21 by B16 F10 melanoma cells documented the elevated infiltration of TREG cells and myeloid‐derived suppressor cells into tumours and found that CCL21 may be a driver of lymphoid neogenesis and immunosuppression, resulting in melanoma cell proliferation 109 …”
Section: The Ccr7/ccl21 Axismentioning
confidence: 96%
“…This suggests that the effect of VEGF-C-enhanced antitumor immunotherapy is somewhat dependent on the CCL21/CCR7 axis. On the other hand, certain CCR7-expressing tumor cells can also use this to undergo lymphatic metastasis, leading to tumor spread and metastasis [202]. Ding et al found an association between high CCR7 expression and lymph node metastasis and poor prognosis in esophageal squamous cell carcinoma [203].…”
Section: Dual Role Of Cerebral Lymphatic System In Brain Metastasis F...mentioning
confidence: 99%